Ecological Disaster in Northern Sumatra: How Extreme Rainfall and Land-Cover Disturbance Triggered Widespread Flash Flooding - Nasri, Nasri; Nursaputra, Munajat; Arif, Abdur Rahman; Dwiyani, Risye; Chania, Lady; Agastya, Ida Bagus Oka; Arif, Dian Adhetya Arif (Jurnal Penelitian Kehutanan Wallacea, 2025)
In November 2025, Northern Sumatra experienced one of the most extreme flood disasters in recent history, triggered by a rare combination of sustained high-intensity rainfall and long-term land-cover disturbance. Using satellite-based rainfall estimates, historical rainfall records, and land-cover change analysis, this study examines the spatial and temporal dynamics of the event. The rainfall produced over 950 mm within four days, with daily accumulation exceeding 390 mm and hourly peaks surpassing 40 mm/hr. Statistical analysis using the Generalized Extreme Value (GEV) distribution estimated a return period of approximately 192 years for the daily maximum. Land-cover analysis revealed extensive deforestation between 1990 and 2024, including in designated protection and conservation forest zones. Flood impacts were concentrated in watersheds with high forest loss and recent land disturbance, particularly in Aceh and North Sumatra. This study highlights how compounding hydroclimatic extremes and upstream land degradation can significantly amplify flood risk. The findings underscore the importance of integrating forest conservation and multi-day rainfall indicators into regional flood risk assessments and early warning systems.